Self Compassion and Social Support as Determinants of Quarter-Life Crisis in Final-Semester Nursing Students - Ananda Putri Budiani; Meida Laely Ramdhani; Isna Hikmawati; Etlidawati (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
Early adulthood is a transitional phase that is vulnerable to academic pressure, career determination, and future uncertainty, so that final year students have the potential to experience a quarter-life crisis (QLC). This phenomenon reflects psychosocial issues that have not been optimally addressed. This study analyzed the effect of self-compassion and social support on QLC in final semester nursing students. The research design used was a quantitative cross-sectional study with 160 respondents selected purposively from a total of 246 students. Data collection instruments included the Quarter-life Crisis Scale, Self-Compassion Scale , and Multidimensional Scale of Perceived Social Support . Data analysis was performed using descriptive statistics and Spearman correlation. The results showed that self-compassion and social support were in the moderate category, while the level of QLC tended to be high. There was a significant negative relationship between self-compassion and QLC (? = -0.699; p = 0.000) and between social support and QLC (? = -0.400; p = 0.000). These findings confirm that low self-compassion and social support contribute to increased QLC in final semester nursing students. The research results indicate the need for promotive and preventive interventions to strengthen these psychosocial protective factors